Worst‐Case Severe Environments for Surface Charging Observed at LANL Satellites as Dependent on Solar Wind and Geomagnetic Conditions - N. Yu Ganushkina; B. Swiger; S. Dubyagin; J.‐C. Matéo‐Vélez; M. W. Liemohn; A. Sicard; D. Payan (Space Weather)
Abstract The 400 worst‐case severe environments for surface charging detected at Los Alamos National Laboratory satellites during the years of 1990–2005 as binned by the definitions of four criteria developed by Matéo‐Vélez et al. (2018, https://doi.org/10.1002/2017sw001689) and the solar wind and Interplanetary Magnetic Field (IMF) parameters and geomagnetic activity indices are analyzed. The conducted analysis shows that only Auroral Electrojet/Auroral Lower index determines the highest risk for severe environments for surface charging to happen. The presence of a substorm with the southward turning pattern in IMF Bz indicates that the environment can be severe for surface charging to occur but this environment will not depend on whether a substorm was moderate or intense. No clear dependence on IMF Bz is found for risk to a severe environment to occur. Appearances of severe environments for surface charging do not necessarily require high values of Kp (Planetarische Kennziffer) and no storm is needed for such an event to be detected. Among solar wind parameters, solar wind velocity Vsw is directly related to the highest risk of severe environments, dependent on the Vsw value; and number density Nsw is of no importance. Two criteria for severe environment events based on the enhancements of low energy particle fluxes exhibit clearer dependencies on the solar wind and IMF parameters and geomagnetic activity indices with more distinct patterns in their time history.